Absence of effect of steady state bempedoic acid on cardiac repolarization: Results of a thorough QT/QTc study in healthy volunteers - Amore, Benny M.; Cramer, Clay T.; MacDougall, Diane E.; Sasiela, William J.; Emery, Maurice G. (Clinical and translational science, 2021)
Bempedoic acid is an inhibitor of adenosine triphosphate–citrate lyase approved for use in adults with hypercholesterolemia. Nonclinical studies assessed binding to the human ether‐a‐go‐go–related gene (hERG) potassium channel in vitro and the effect of bempedoic acid on QT/QTc in cynomolgus monkeys. A randomized, double‐blind, parallel‐design clinical study assessed the effects of steady‐state bempedoic acid at a supratherapeutic dose (240 mg/day, 33.3% higher the180 mg/day therapeutic dose), placebo, and moxifloxacin (400 mg) in healthy subjects. In vitro binding potency for bempedoic acid to the hERG potassium channel was weak, with half‐maximal inhibition (IC50) estimated at greater than 1000 μM (>1670‐fold the bempedoic acid 180 mg/day steady‐state unbound maximum concentration). In monkeys, individual rate‐corrected QT intervals showed no time‐ or dose‐dependent changes up to 100 mg/kg of bempedoic acid. In human subjects, the upper 90% confidence interval (CI) for the difference in QTc interval, corrected using Fridericia’s formula (QTcF), between bempedoic acid and placebo was less than 5 msec at all time points. Concentration‐QTcF analysis showed that maximum bempedoic acid concentration at steady‐state was attained at a median 2.1 h postdose, and the predicted mean change (90% CI) in QTcF at the observed mean bempedoic acid concentration 2 h postdose was −0.5 (−5.0, 4.0) msec. The lower bound of the moxifloxacin 90% CI exceeded 5 msec at prespecified time points, establishing study sensitivity. Steady‐state bempedoic acid at a supratherapeutic dose of 240 mg was generally well‐tolerated and not associated with QTc prolongation in healthy subjects.